PENERAPAN METODE ROLE PLAYING DALAM PEMBINAAN AKHLAK SISWA DI SMA NEGERI 1 TANJUNG TIRAM KABUPATEN BATU BARA - Muhammad Arifin (UIN Sumatera Utara Medan, 2017)
The main purpose of this research is to know the application of role playing methode in the effort of morality of students in Public senior high school 1 Tanjung Tiram, how use the methods, evaluation, what are the constraining factors and supporters in the application of active learning model in this school. The benefit of this research is to give thought contribution for Local Government, Education Office, and School Party about the implementation of active learning model in Public senior high school 1 Tanjung Tiram and its relation to moral guidance in Public senior high school 1 Tanjung Tiram, Batu Bara Regency.This thesis research uses qualitative method. The data collection process is done by observation technique, in-depth interview, and documentation study. In analyzing the data, researchers used qualitative analysis techniques with data exposure measures, data reduction, conclusions. This study was conducted by triangulation of data. While the technique of guaranteeing the validity of data is done with credibility, transferability, and confrmability.The results of this study inform many of the things as follows: namely; (1). Rol playing method is aplicated in Public senior high school 1 Tanjung Tiram which is a concrete manifestation of the National Curriculum, in this curriculum is more emphasizing aspects of spiritual and social attitudes that expect the morality of students in the school. (2) The process of moral coaching of students is more focused on Islamic Subject Teachers and Teacher Counseling Guidance that is more participate and responsible for morals students in school.